Move all terms not containing `x` to the right-hand side of the equation.

`1/2 x + 5/12 = 1/6`

Move all terms not containing `x` to the right-hand side of the equation.

`1/2 x = -1/4`

Multiply `-1` by `2` to get `-2` .

`x=-2/4`

Reduce the expression by canceling out all common factors from the numerator and denominator.

`x=-1/2`

` `

`x+5/12=x/2+1/6`

`x+5/12-x/2=x/2+1/6-x/2`

`x-x/2+5/12-5/12=1/6-5/12`

`x-x/2=1/6-5/12`

`12(x-x/2)=12(1/6-5/12)`

`12x-12 xx x/2=12xx1/6-12xx5/12`

`12x-6x=2-5`

`6x=-3`

`(6x)/6=(-3)/6`

`x=-3/6`

`=-1/2`

QUESTION:-

x + 5/12 = x/2 + 1/6

SOLUTION:-

In order to solve this problem, we first have to make the denominators same so that numerators can be added;

(12x + 5) /12 = (3x + 1) /6

Now transpose both the sides denominators to opposite side of numerator;

(12x + 5) . 6 = (3x + 1) . 12

72x + 30 = 36x + 12

Now take the integers with x on LHS and integers with no x are supposed to be transferred to RHS;

72x - 36x = 12 - 30

36x = - 18

x = -18/36

x = -1/2

OR

x = - 0.5

Therefore the answer in decimal form is -0.5 and in fraction form is -1/2.

Hence Solved!

SOLUTION:

`x+(5/12) = (x/2) + (1/6)`

Taking L.C.M:

Multiplying by 6 on both sides:

`{x+(5/12)}*6 = {(3x+1)/6}*6`

Thus, after multiplication:

`6x+{(5*6)/12} = 3x+1`

` <br> `

``

`6x-3x=1-(30/12)`

`3x= 1-(5/2)`

`3x=1-2.5`

`3x=-1.5`

`x=-1.5/3`

`x=-0.5`

` `

``Therefore, the above question's answer is -0.5 or in other words, in the form of fraction, it would be -1/2. The easiest way to solve such problems is to take each thing step by step, and letting your mind be at ease before trying to solve.

` `